Spatial Changes in Soil Nutrients in Tea Gardens from the Perspective of South-to-North Tea Migration: A Case Study of Shangluo City - Ziqi Shang; Jichang Han; Yonghua Zhao; Ziru Niu; Tingyu Zhang (Land, 2025)
[Objective] This study focused on the primary tea-producing regions of Shangluo City (ranging from 108°34′20″ E to 111°1′25″ E and 33°2′30″ N to 34°24′40″ N), which include Shangnan County, Zhen’an County, Zhashui County, Danfeng County, and Shanyang County. The aim was to explore the characteristics and influencing factors of soil nutrient content variation across different tea gardens in the area. The study involved an analysis of various soil nutrient indicators and an investigation of their correlations to assess the nutrient status of tea gardens in Shangluo City. [Method] A total of 228 soil samples from these tea gardens were quantitatively analyzed for pH, soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), total potassium (TK), available nitrogen (AN), available phosphorus (AP), available potassium (AK), as well as clay, silt, and sand content. Additionally, the soil texture was qualitatively analyzed. Statistical methods including analysis of variance (ANOVA), correlation analysis, principal component analysis (PCA), and regression analysis were performed using SPSS software to examine the relationships between soil nutrients and texture in relation to altitude, latitude, and fertility status. [Results] The results indicated that the pH of tea garden soils in Shangluo City was relatively stable, ranging from 4.3 to 7.6, with the mean of 5.9 and a coefficient of variation of 11.0%. The soil organic matter (SOM) content varied from 7.491 to 81.783 g/kg, exhibiting a moderate variability with a coefficient of variation of 38.75%. The mean values for total nitrogen (TN), available nitrogen (AN), total phosphorus (TP), available phosphorus (AP), total potassium (TK), available potassium (AK), clay, silt, and sand were 1.53 g/kg, 213 mg/kg, 0.85 g/kg, 49.1 mg/kg, 5.5 g/kg, 110 mg/kg, 3.99, 44.89, and 51.11, respectively. AN and AP displayed higher coefficients of variation at 57% and 120.1%, respectively. Significant differences in pH, SOM, TN, TP, TK, silt, and sand were observed at varying elevations, while TN, TP, TK, clay, silt, and sand varied significantly across different latitudes. Principal component analysis (PCA) results revealed that altitude had four principal components with eigenvalues greater than 1, accounting for 71.366% of the total variance, whereas latitude exhibited five principal components with eigenvalues exceeding 1, explaining 76.304% of the total variance. Regression analysis indicated that altitude exerted a stronger influence on soil indicators, as demonstrated by a well-fitting model (Model 4), where the coefficients of principal components 1, 3, and 4 were positive, while that of principal component 2 was negative. In contrast, latitude influenced soil indicators most effectively in Model 3, where the coefficient of principal component 5 was positive, and the coefficients of principal components 1 and 4 were negative. [Conclusions] The variation in soil nutrients and pH in the tea gardens of Shangluo City is closely associated with altitude and latitude. Notably, there is no discernible trend of pH acidification. Therefore, tea garden management should prioritize the rational application of soil nutrients at varying altitudes and focus on enhancing soil texture at different latitudes to adapt to the diverse soil characteristics under these conditions, thereby promoting sustainable development in tea gardens.